Method for producing battery composite material and precursor thereof
The method of reacting phosphoric acid with iron powder to produce LFP-NCO battery materials simplifies the manufacturing process, reduces impurity separation needs, and aligns with environmental sustainability by minimizing waste and raw material costs.
Patent Information
- Application Number
- JP2023099845
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-09-05
- Filing Date
- 2023-06-19
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-06-19
AI Technical Summary
The manufacturing process of nanomicron metal oxide eutectic lithium iron phosphate (LFP-NCO) battery materials faces challenges in controlling pH value, treating by-products, and managing impurities, which affect product quality and increase costs, while not aligning with environmental protection standards.
A method involving the reaction of phosphoric acid with iron powder to form a slurry, followed by polishing, drying, and firing with air or oxygen introduction, eliminating the need for separate impurity separation steps and reducing raw material costs by using iron, phosphorus, and lithium compounds without additional elements.
This process simplifies the manufacturing, reduces sensitivity to pH control, shortens the process time, and enhances product quality, aligning with environmental sustainability by minimizing waste and raw material consumption.
Smart Images

Figure 0007617182000002 
Figure 0007617182000003 
Figure 0007617182000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a battery composite material, in particular to a method for producing a battery composite material and a precursor thereof. [Background technology]
[0002] With the progress of science and technology, the development of electronic products and transportation equipment has brought great convenience to modern life. In recent years, environmental protection awareness has been attracting worldwide attention, and how to reduce energy consumption while maintaining the convenience of life has become the goal of current industrial development. The energy storage technology of secondary batteries has attracted much attention and is developing rapidly.
[0003] Lithium iron phosphate (LiFePO 4 Lithium iron phosphate (LFP) battery materials are the most widely used, and have the advantages of low cost, high safety, low environmental pollution, high current charge and discharge resistance, and the raw materials are relatively inexpensive, making them very suitable for use in high-power products such as electric vehicles that require high current and large capacity. However, to overcome the problems of low conductivity and high impurities in conventional lithium iron phosphate batteries, nano-micron metal oxide eutectic lithium iron phosphate compound (LFP-NCO) battery materials with a single structure consisting of phosphorus, lithium, and iron have been developed.
[0004] In the production process of LFP-NCO, iron salts (such as iron nitrate and iron sulfate) are often used as raw materials, mixed with phosphates, and nitrogen gas is introduced to produce iron phosphate, which is then reacted with lithium hydroxide, lithium carbonate, or other complexes containing lithium atoms. However, in the production process of iron phosphate, salt by-products and impurities are often produced due to the inclusion of groups such as nitrate and sulfate groups and the involvement of nitrogen. Therefore, a separate separation step must be performed to separate the salt by-products and impurities from the iron phosphate to avoid the corrosion of the equipment caused by the gas by-products generated by groups such as nitrate and sulfate during the subsequent calcination, and the salt by-products must be further treated by special procedures after separation. In the production process of iron phosphate, not only must attention be paid to the pH value of the reaction environment, but also the salt by-products generated during the reaction must be removed. Otherwise, it will affect the quality of the product and the by-products must be treated. This not only increases the cost, but also does not comply with current environmental protection. Summary of the Invention [Problem to be solved by the invention]
[0005] In the manufacturing process of the above-mentioned nano-micron metal oxide eutectic lithium iron phosphate compound (LFP-NCO) battery material, in order to overcome the problems of the difficulty of the process and waste disposal due to the need for pH value control and by-product disposal, as well as the impact on product quality, the present invention provides a manufacturing method for a battery composite material. [Means for solving the problem]
[0006] The method for producing a battery composite material provided by the present invention includes the steps of: Step 1: reacting a compound capable of releasing phosphate ions with iron powder to produce a first product in the form of a slurry; After grinding, drying and calcination, the chemical formula is FePO 4 Step 2 of generating a precursor, The precursor is reacted with a first reactant having lithium atoms and a carbon source having carbon atoms to form a compound having the formula LiFePO 4Step 3 of forming a battery composite material, Including, Air or oxygen is directly introduced during firing.
[0007] In the present invention, in step 3, a metal oxide is added and reacted to form LiFePO having the metal oxide. 4 The battery composite material, a nano-micron metal oxide eutectic lithium iron phosphate compound (LFP-NCO), is formed.
[0008] In the present invention, the metal oxide is vanadium pentoxide (V 2 O 5 ) or magnesium oxide (MgO).
[0009] In the present invention, the compound is phosphoric acid, and the chemical formula of the first product is a-FePO 4 xH 2 O and x is greater than 0.
[0010] In the present invention, the first reactant is lithium carbonate (Li 2 CO 3 ), lithium hydroxide (LiOH), or a mixture of lithium-containing compounds.
[0011] In the present invention, the carbon source may be a sugar, an organic compound, a polymer or a polymeric material.
[0012] In the present invention, the saccharide may be the monosaccharide fructose, glucose or galactose, or the disaccharide maltose, sucrose, lactose, and the polymer material is polyvinylpyrrolidone (PVP).
[0013] Furthermore, step 2 includes: grinding the first product until the average particle size (D50) of the first product is less than 5 microns (μm); spray drying the ground first product to form a powder; introducing said air or said oxygen to calcinate said powder to form said precursor.
[0014] Furthermore, the first product is polished at a rotation speed of 450 to 650 revolutions per minute (rpm), Spray drying is performed using a rotary disk spray dryer, and the rotary disk spray dryer has an inlet temperature of 180 to 230°C; The outlet temperature is 80 to 100°C. The rotation speed of the rotary spray dryer is 350 Hz, the calcination temperature of the powder is 550 to 700° C., and the calcination time is 30 minutes to 1.5 hours.
[0015] The first product has an average particle size (D50) of less than 2 microns (μm); The rotation speed is 550 revolutions per minute, The inlet temperature is 200 to 220°C, The outlet temperature is 85 to 95°C, The firing temperature is 600 to 650°C.
[0016] The present invention further relates to a compound having the formula FePO 4 A precursor having the formula LiFePO is reacted with a first reactant having lithium atoms and a carbon source having carbon atoms. 4 The present invention provides a method for producing a battery composite material, which forms a battery composite material comprising:
[0017] The present invention further includes the steps of reacting iron powder with a compound capable of releasing phosphate ions to produce a first product in a slurry form; A precursor is produced by grinding, drying and calcining, and the chemical formula of the precursor is FePO 4 and The present invention provides a method for producing a precursor of a battery composite material comprising: Effect of the Invention
[0018] The method for preparing the battery composite material and its precursor provided by the present invention not only simplifies the process, but also allows the battery composite material to be prepared without being limited to the use of lithium hydroxide as the lithium compound, reduces the sensitivity of the pH value of the process, reduces the difficulty of the process, and greatly shortens the overall process time. In addition, by using phosphoric acid, deionized water and iron powder reaction, and air introduction technology during calcination, the raw material cost can be effectively reduced under the premise of sufficient reaction between the phosphoric acid aqueous solution and the iron powder. Since there are no additional elements that may remain in the finished product, no additional process is required to separate impurities, the atomic utilization rate from the raw materials to the finished product is extremely high, and there is no waste disposal problem, which is in line with the current trend of attaching importance to environmental protection and sustainable manufacturing. [Brief description of the drawings]
[0019] [Figure 1] 2 is a flow chart of a manufacturing method of a preferred embodiment of the present invention. [Diagram 2] 1 is a first detailed flowchart of a preferred embodiment of the present invention. [Diagram 3] 2 is a second detailed flowchart of a preferred embodiment of the present invention. [Figure 4] FIG. 2 is an X-ray diffraction diagram of a precursor of a preferred embodiment of the present invention. [Diagram 5] FIG. 2 is an X-ray diffraction diagram of a precursor of a comparative example of the present invention. [Figure 6A] 1 is a scanning electron microscope image of a precursor of an embodiment of the present invention. [Figure 6B] 1 is a scanning electron microscope image of a comparative precursor of the present invention. [Figure 7A] 1 is a scanning electron microscope image of the precursor of the first preferred embodiment of the present invention; [Figure 7B] 1 is a scanning electron microscope image of a precursor of a second preferred embodiment of the present invention; [Figure 8A] 1 is a scanning electron microscope image of a precursor of a first comparative example of the present invention. [Figure 8B] 1 is a scanning electron microscope image of a precursor of a second comparative example of the present invention. [Figure 9]FIG. 2 is a charge / discharge electrical characteristic diagram of a finished product according to a preferred embodiment of the present invention. [Figure 10] FIG. 13 is a diagram showing charge and discharge electrical characteristics of a finished product according to a comparative example of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] 1 is a flow chart of the method for producing a battery composite material provided by the present invention, the steps of which include:
[0021] S1, phosphate (H 3 PO 4 ), iron powder (Fe), a carbon source, and a first reactant are provided. The carbon source may be a sugar, an organic compound, a polymer, or a polymeric material that includes carbon atoms. The first reactant is a compound that includes lithium atoms.
[0022] The carbon source is exemplified by the sugars, which may be the monosaccharides fructose, glucose or galactose, or the disaccharides maltose, sucrose or lactose.
[0023] The carbon source may be, for example, polyvinylpyrrolidone (PVP), such as the polymer material.
[0024] The first reactant is lithium carbonate (Li 2 CO 3 ), lithium hydroxide (LiOH), or a mixture of several lithium-containing compounds.
[0025] S2, generation of first product: reacting phosphoric acid with iron powder to generate a first product, the first product being in the form of a slurry and having the chemical formula a-FePO4·xH 2 O and x is greater than 0.
[0026] S3, Precursor formation: through grinding, drying and calcination, a precursor with the chemical formula FePO4 is produced. Here, during calcination, instead of the traditional nitrogen gas calcination process, air or oxygen is directly introduced, which simplifies the steps and reduces the cost.
[0027] S4. Formation of battery composite material: The precursor and the first reactant are reacted together through grinding, drying, calcination, etc., to form a powder with the chemical formula LiFePO 4 In this step, the carbon source is added at the same time to form a carbon-coated surface on the battery composite, which can achieve better electrical conductivity.
[0028] In step S4, vanadium pentoxide (V 2 O 5 Metal oxides such as magnesium oxide (MgO) and LiFePO 4 A battery composite material, namely nano-metal oxide co-crystallized lithium iron phosphate compound (LFP-NCO), can be produced.
[0029] The method for preparing the battery composite material provided by the present invention is to directly use iron powder as a reactant and react it with phosphoric acid to form the battery composite material. In the whole process, no extra elements are contained except for lithium, iron, phosphorus and oxygen, and in the reaction process, only hydrogen ions of phosphoric acid are converted into hydrogen and dissipated into the atmosphere, which not only has a high atomic utilization rate but also meets the current environmental protection requirements, and does not generate by-products, so there is no need to perform a separate separation step in the subsequent process.
[0030] The manufacturing method of the battery composite material provided by the present invention not only does not involve any extra elements, but also directly introduces the air or oxygen, so that no by-products are generated during the process, there is no risk of impurities being mixed into the battery composite material, and the occurrence of a situation that may destroy the device during the subsequent firing process can be avoided.
[0031] Furthermore, please also refer to the first detailed flowchart of step S2 shown in Figure 2. The steps are as follows.
[0032] S201, forming a first phosphoric acid solution: At a first temperature, the phosphoric acid is measured using deionized water to form a first phosphoric acid solution, wherein the first temperature is maintained at 40-50°C, preferably 42°C.
[0033] S202, Iron powder reaction: reacting the first phosphoric acid solution with iron powder at a second temperature, lowering the temperature to a third temperature and holding for a first reaction time, where the second temperature is below 60° C., preferably 60° C.; the third temperature is below 50° C., preferably 50° C.; and the first reaction time is at least 3 hours.
[0034] S203, forming the first product: quantitating the phosphoric acid using deionized water to form a second phosphoric acid solution. At a fourth temperature, the second phosphoric acid solution is added to the mixture generated after step S202 and allowed to stand for a second reaction time to form an iron phosphate slurry, the iron phosphate slurry including at least a phosphoric acid radical, an iron ion, and the first product consisting of phosphoric acid, iron, and water, and having a chemical formula of a-FePO 4 xH 2 The time required is O(x>0).
[0035] wherein the fourth temperature is below 30° C., preferably 30° C., and the second reaction time is maintained for at least 23 hours.
[0036] Here, the weight ratio of the first phosphoric acid solution and the second phosphoric acid solution after measurement is 3:1, that is, when the weight of the first phosphoric acid solution after measurement is 75%, the weight of the second phosphoric acid solution after measurement is 25%.
[0037] In steps S202 and S203, phosphate ions are released and react with the iron powder. Similarly, other compounds that can release phosphate ions after mixing can be used instead of the first phosphoric acid solution or the second phosphoric acid solution.
[0038] Through steps S202 and S203, after the iron powder is exposed to the conditions of different concentrations of phosphoric acid solutions, different temperatures and different reaction times, the iron powder can completely react with the phosphoric acid radicals to produce the first product, effectively avoiding material waste.
[0039] Then, after step S2, a second detailed flow chart of step S3 provided in Figure 3 is combined. The steps include:
[0040] S301, Polishing: Polishing the first product using a first rotation speed until the average particle size (D50) of the first product is less than 5 microns (μm), preferably less than 2 microns (μm), the first rotation speed being 450 to 650 revolutions per minute (rpm), preferably 550 revolutions per minute.
[0041] S302, Drying: Spray-dry the ground first product through a rotary spray dryer to form a powder, where, but not limited to, the inlet temperature of the rotary spray dryer is 180-230°C, preferably 200-220°C, the outlet temperature is 80-100°C, preferably 85-95°C, and the rotation speed is 350Hz.
[0042] S303, forming a precursor by ventilating and calcining: calcining the dried powder and stirring it in a timely manner to ensure that the powder is in sufficient contact with the air or oxygen, and forming the precursor (FePO 4) is formed. It should be noted that since air or oxygen can be directly introduced during calcination, there is no need to add other extra elements, replacing the conventional calcination process that requires nitrogen gas, simplifying the steps and reducing costs. The calcination temperature is 550 to 700°C, preferably 600 to 650°C, and the calcination time is less than 3 hours, preferably 30 minutes to 1.5 hours. In this step, the powder is calcined through the air or oxygen, so that the phosphate radicals, the iron ions and the first product in the powder are sufficiently bonded and dehydrated to form the pure precursor FePO 4 can be obtained.
[0043] The present invention further provides a detailed flow for forming the battery composite material by reacting the precursor and the first reactant together in step S4, which includes the following steps:
[0044] Polishing: Polish the precursor and the first reactant using a second rotation speed until the average particle size (D50) of the mixture of the precursor and the first reactant is less than 2 microns (μm), preferably less than 1 micron (μm). The second rotation speed is 450 to 650 revolutions per minute (rpm), preferably 550 revolutions per minute.
[0045] Drying: Spray-dry the mixture of the ground precursor and the first reactant by a rotary spray dryer to form a second powder, where, but not limited to, the inlet temperature of the rotary spray dryer is 170-250°C and the outlet temperature is 70-110°C.
[0046] Sintering: Nitrogen gas is introduced to sinter the second powder, and the powdered battery composite material LiFePO 4 Form.
[0047] The battery composite material has low cost and simple steps, and does not require special and expensive reaction raw materials, which can reduce costs, overcome the process difficulties of controlling the pH value and temperature of the reaction environment in the production of conventional battery materials, avoid excessive consumption of raw materials, and improve product quality.
[0048] 4 to 8B, the following illustrative examples are provided using the above steps, and compared with a comparative example in which nitrogen gas is introduced during firing. Here, in Example 1, the air is introduced in step S303 to perform firing, and in Example 2, in addition to introducing the air in step S303 to perform firing, the metal oxide vanadium pentoxide is further added and reacted in step S4. In Comparative Example 1, the nitrogen gas is introduced in step S303 to perform firing, and in Comparative Example 2, the metal oxide vanadium pentoxide is further added and reacted in step S4.
[0049] <Example 1> Prepare 3,196 g of phosphoric acid, 10 L of deionized water, and 2,532 g of iron powder. Then, perform steps S2 and S3 to obtain FePO 4 The precursor is further analyzed by X-ray diffraction (XRD), and the results are shown in Figure 4. Comparing with the standard diffraction pattern (JCPDS Card), the structure is FePO 4 It is confirmed that the surface morphology is the same as that of the FePO 1056 g obtained above. The surface morphology is analyzed by scanning electron microscope (SEM) analysis shown in FIG. 6A. 4 Precursor and 264 grams of lithium carbonate Li 2 CO 3 was reacted with 49 grams of fructose and 25 grams of polyethylene glycol to form a first example LFP battery composite, the surface morphology of which was analyzed by scanning electron microscopy (SEM) and is shown in FIG. 7A.
[0050] <Example 2> Prepare 3,196 g of phosphoric acid, 10 L of deionized water, and 2,532 g of iron powder. Then, perform steps S2 and S3 to obtain FePO 4 Next, 1056 grams of the FePO 4 and 264 grams of lithium carbonate, Li 2 CO 3 of 49 grams of fructose, 25 grams of polyethylene glycol and 2.7 grams of vanadium pentoxide. 2 O 5 to form a battery composite, designated as second example LFP-V, whose surface morphology was analyzed by scanning electron microscopy (SEM) as shown in FIG. 7B.
[0051] <Comparative Example 1> 3196 g of phosphoric acid, 10 liters of deionized water, and 2532 g of iron powder are prepared. Then, proceed to steps S2 and S3 to produce the first product. The difference from the embodiment is that in step S3, nitrogen gas is introduced when forming the precursor by firing, and finally, the molecular formula Fe 7 (PO 4 ) 6 The result of X-ray diffraction (XRD) analysis of the precursor of this comparative example is shown in FIG. 6B. When compared with the standard diffraction pattern (JCPDS Card), the structure was found to be Fe 7 (PO 4 ) 6 It is confirmed that the surface morphology is the same as that of the precursor Fe. The surface morphology of the precursor Fe was analyzed by scanning electron microscope (SEM) analysis shown in FIG. 6B. 7 (PO 4 ) 6 and 264 grams of lithium carbonate Li 2 CO 3 was reacted with 49 grams of fructose and 25 grams of polyethylene glycol to form a battery composite material, designated as Comparative Example 1 LFP-N. The surface morphology analyzed by scanning electron microscopy (SEM) is shown in FIG. 8A.
[0052] <Comparative Example 2> 3196 g of phosphoric acid, 10 liters of deionized water, and 2532 g of iron powder are prepared. Then, proceed to steps S2 and S3 to produce the first product. The difference from the embodiment is that in step S3, nitrogen gas is introduced when forming the precursor by firing, and finally, the molecular formula Fe 7 (PO 4 ) 6 Next, 1056 g of the precursor Fe obtained above was 7 (PO 4 ) 6 of 49 grams of fructose, 25 grams of polyethylene glycol and 2.7 grams of vanadium pentoxide. 2 O 5 to form a battery composite material, designated as Comparative Example 2 LFP-VN. The surface morphology analyzed by scanning electron microscopy (SEM) is shown in FIG. 8B.
[0053] Comparing Figures 4 and 5, the noteworthy point in Figure 5 is the presence of several waveforms X that are not included in the standard diffraction pattern (JCPDS Card). 7 (PO 4 ) 6 It can be assumed that the precursor of the present invention contains other iron compounds. When preparing the precursor, the raw material ratio of the iron powder and the phosphoric acid is such that the molar ratio of iron atoms to phosphorus atoms is 1:1, which is the same as the molar ratio of iron atoms to phosphorus atoms in the precursor produced after sintering in the embodiment of the present invention. However, in the comparative example, on the premise that it is not possible to know what the iron compound is from the standard diffraction pattern (JCPDS Card), the precursor Fe 7 (PO 4 ) 6 Since the molar ratio of iron atoms to phosphorus atoms is not 1:1 as described above, the precursor Fe 7 (PO 4 ) 6 This is because it can be assumed that other iron compounds are also produced at the same time as the formation of the iron compound. Furthermore, it can be shown by comparison that the method for producing a battery composite material provided by the present invention can achieve excellent atomic utilization.
[0054] 4 to 8B and Table 1 below, the following can be observed. 7 (PO 4 ) 6 The precursor is composed of smaller particles, has more pores, and has a density of about 7.4 square meters per gram (m 2 / g), and the specific surface areas of the first comparative LFP-N and the second comparative LFP-VN produced by further reaction are 17.77 square meters per gram (m 2 / g) and 17.50 meters squared / gram (m 2 / g). The FePO 4 The precursor has large particles, few pores, and a specific surface area of approximately 3.5 square meters per gram (m 2 / g), and the specific surface area of the first embodiment LFP and the second embodiment LFP-V produced by further reaction is 8.21 square meters per gram (m 2 / g) and 9.69 square meters / gram (m 2 / g). The precursors (FePO 4 ) and the specific surface area of the battery composite materials (LFP and LFP-V) were compared with the precursors (Fe 7 (PO 4 ) 6 ) and its battery composite materials (LFP-N and LFP-V-N). 4 It can be seen that because the precursor has a relatively high overall packed density, the battery composites produced therefrom can provide relatively high energy densities.
[0055] [Table 1]
[0056] The battery composite materials obtained in Example 1 and Comparative Example 1 were used as the first coin cell and the second coin cell, respectively, and electrical tests were carried out using a charger and discharger for two cycles of 0.1 coulomb charge and discharge and two cycles of 2 coulomb charge and discharge. The test results for the first coin cell are shown in FIG. 9 and the second coin cell are shown in FIG. 10. FePO 4 The first coin cell and Fe 7 (PO 4 ) 6 It can be seen that the cut-off voltages of the second coin cells manufactured in the above are both 2 to 4.2 volts, and the discharge rates are the same for both. However, it is clear from the discharge curves of the first coin cells that the capacity of the first coin cells is superior, making them suitable for use in energy storage lithium batteries and achieving longer usage times.
[0057] The method for preparing the battery composite material and its precursor provided by the present invention not only has a simple process, but also allows the preparation of the battery composite material without being limited to the lithium compound using lithium hydroxide, thereby reducing the sensitivity of the process to pH, reducing the process difficulty, and greatly shortening the overall process time.
[0058] In addition, by using the reaction of phosphoric acid, deionized water and iron powder, and the technology of introducing air during calcination, raw material costs can be effectively reduced under the premise of sufficient reaction between the phosphoric acid aqueous solution and iron powder. Since there are no additional elements that may remain in the finished product, no additional process is required to separate impurities, and the utilization rate of atoms from the raw materials to the finished product is extremely high, and no waste disposal problems arise, which is in line with today's trend of pursuing environmental protection and sustainable manufacturing. [Explanation of symbols]
[0059] LFP 1st Example LFP-V 2nd Example LFP-N 1st comparative example LFP-V-N 2nd comparative example X Unrecorded waveforms
Claims
1. Step 1: reacting a compound capable of releasing phosphate ions with iron powder to produce a first product in the form of a slurry; After grinding, drying and sintering, the chemical formula was determined to be FePO 4 Step 2 of producing a precursor, The precursor is reacted with a first reactant having lithium atoms and a carbon source including carbon atoms to form a compound having the formula LiFePO 4 Step 3 of forming a battery composite material, Including, A method for producing a battery composite material, in which air or oxygen is directly introduced during firing.
2. In step 3, a metal oxide is added and reacted to obtain LiFePO having the metal oxide. 4 10. The method of claim 1 for producing a battery composite material, which forms a nano-micron lithium iron phosphate eutectic metal oxide compound (LFP-NCO) battery composite material.
3. The metal oxide is vanadium pentoxide (V 2 O 5 3. The method for producing a battery composite material according to claim 2, wherein the material is selected from the group consisting of arsenic (Ar) and magnesium oxide (MgO).
4. The compound is phosphoric acid and the formula of the first product is a-FePO 4 ・xH 2 O, x is greater than 0, The first reactant is lithium carbonate (Li 2 CO 3 ), lithium hydroxide (LiOH), or a mixture of lithium-containing compounds; The method for producing a battery composite material according to claim 1 or 2, wherein the carbon source is one of a sugar, an organic compound, a polymer, or a polymeric material.
5. 5. The method of claim 4, wherein the sugar is one of monosaccharides fructose, glucose or galactose, disaccharides maltose, sucrose or lactose, and the polymer material is polyvinylpyrrolidone (PVP).
6. Step 2 includes: grinding the first product until the average particle size (D50) of the first product is less than 5 microns (μm); spray drying the ground first product to form a powder; The method for producing a battery composite material according to claim 1 , further comprising introducing the air or the oxygen to calcinate the powder to form the precursor.
7. grinding the first product at a rotational speed of 450 to 650 revolutions per minute (rpm); Spray drying is carried out using a rotating disk spray dryer, the rotating disk spray dryer comprising: The inlet temperature is 180-230°C. The outlet temperature is 80 to 100°C. The rotation speed of the rotating disk spray dryer is 350 Hz; The method for producing a battery composite material according to claim 6, wherein the powder is sintered at a temperature of 550 to 700° C. for a period of 30 minutes to 1.5 hours.
8. The first product has an average particle size (D50) of less than 2 microns (μm); The rotation speed is 550 revolutions per minute, The inlet temperature is 200 to 220° C. The outlet temperature is 85 to 95° C. The method for producing a battery composite material according to claim 7, wherein the sintering temperature is 600 to 650°C.
Citation Information
Patent Citations
Method for preparing lithium ferrous phosphate
CN101693532A
Fiber-ball-shaped lithium manganese phosphate anode material of lithium ion battery and preparation method of fiber-ball-shaped lithium manganese phosphate anode material
CN102610816A
Method for manufacturing composite materials for batteries and their precursors
JP2014524123A
Method for manufacturing battery composite materials and their precursors
JP2016522965A
METHOD OF FABRICATING LiFePO4 CATHODE ELECTROACTIVE MATERIAL BY RECYCLING, AND LiFePO4 CATHODE ELECTROACTIVE MATERIAL, LiFePO4 CATHODE, AND LITHIUM SECONDARY BATTERY FABRICATED THEREBY
US20130313485A1